Immune escape of tumors: apoptosis resistance and tumor counterattack - Igney, Frederik; Krammer, Peter H. (Journal of leukocyte biology, 2002)
Interactions between the immune system and malignant cells play an important role in tumorigenesis. Failure of the immune system to detect and reject transformed cells may lead to cancer development. Tumors use multiple mechanisms to escape from immune-mediated rejection. Many of these mechanisms are now known on a cellular and molecular level. Despite this knowledge, cancer immunotherapy is still not an established treatment in the clinic. This review discusses the immune escape mechanisms used by tumors with an emphasis on mechanisms related to apoptosis.
Gesehen am 02.03.2021
DOI funktioniert nicht